Envisioning democracy : new essays after Sheldon Wolin's political thought - Maley, Terry; Wallach, John R.; Wolin, Sheldon S. (Toronto ; Buffalo ; London : University of Toronto Press, 2023)
"There is no political term today that has a greater cachet and so little clarity than democracy. Leaders of large states use it to designate their nations' public character, while it is also used by critics of leaders calling themselves "democratic" to spearhead their calls for political reforms. In Envisioning Democracy, Terry Maley and John R. Wallach address the following key questions: What does democracy mean today? What could it mean tomorrow? What is the dynamic of democracy, especially in an increasingly interdependent world of growing inequality, that can be captured by authoritarian populist leaders? Envisioning Democracy explores these questions amid the dynamic of democracy as a political phenomenon interacting with forms of economic, ethical, and intellectual life. The book draws on the thought of one of America's greatest writers on democracy in the last fifty years, Sheldon S. Wolin (1922-2015). In this collection, scholars consider the historical conditions, theoretical elements, and practical impediments to democracy, relying on Wolin's insights as touchstones in thinking through what democracy means now and what it could mean in the future. Envisioning Democracy presents new perspectives on longstanding, current, and future issues surrounding democracy and liberalism in political theory."--
Interpreting Democracy in Undemocratic Societies / John R. Wallach -- Aristotle on Enmity: Ideology, Somatic Justice, and Emotions / Ingrid Creppell -- Sheldon Wolin and Democratic "Theory" / Jason Frank -- Wolin on Myth: A Critique / Terence Ball -- Social Amnesia in Canada's TRC: Sheldon Wolin, Radical Indigenous Thought, and the Settler-Colonial Politics of Reconciliation / Calvin L. Lincez -- Realistic Political Education / Stephen Esquith -- Wolin and Said on Political Education, Vision, and Intellectual Tradition / Lucy Cane -- Democracy between Reactionary Tribalism and the Megastate / Iain Webb -- The Historical Fate of Fugitive Democracy Today / Terry Maley -- Transformative Sanctuary: Rethinking Fugitive Democracy and Black Fugitivity with Frontline Communities in the Underground Railroad / Romand Coles and Lia Haro -- Visioning Limits or Unlimited Vision? The Vocation of Political Theory in the Anthropocene / Andrew Biro.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 31, 2023).
eBooks on EBSCOhost
Keywords: Wolin, Sheldon S; Democracy; Political science; POLITICAL SCIENCE / Human Rights; Democracy; Political science; anthropocene; democracy; democratic theory; fugitive democracy; human rights; legal philosophy; political education; political theory; reactionary tribalism; reconciliation; settler colonialism; Electronic books; Electronic books; Festschriften